A comparative philosopher's study and translation of Sun Zi Bing Fa: an interview with professor Roger T. Ames. Issue 1 (2nd January 2020) - Zheng, Jianning
ABSTRACT: Professor Roger T. Ames is a world-renowned comparative philosopher and translator of Chinese classics. He is Humanities Chair Professor at Peking University in Beijing, China and Professor Emeritus of Philosophy at the University of Hawai'i at Mānoa, the United States. His main contributions center around the study of Chinese and comparative philosophy and the translation of Chinese classics, such as Sun Zi Bing Fa, Huai Nan Zi, Sun Bin Bing Fa, Lun Yu, Zhong Yong, Dao De Jing and Xiao Jing . His translation of Sun Zi Bing Fa: Sun Tzu: The Art of Warfare was published in 1993 by Ballantine Books, a division of Random House, New York. He emphasizes the importance of understanding Chinese philosophy on its own terms rather than through the framework of Western philosophy. He received the "Confucius Culture Award" in 2013 and the "Huilin Culture Award" in 2016 for his study and translation of Chinese culture. He also received the "Outstanding Lifetime Achievement Award" from the John Dewey Society in 2019 for his contributions to education and culture. This interview was conducted at Peking University on 1 May 2019 and focused on Sun Zi Bing Fa, the translation of which has become a success in intercultural communications.